ALPHA-1-ANTITRYPSIN – A BIOMARKER OF ANTIPROTEASE PROTECTION IN THE PREDICTION OF PREMATURE BIRTH IN COVID-19 AND HEALTHY PREGNANT WOMEN - Komarevtseva, I.O.; Chernykh, Yu.A.; Cherednichenko, R.V.; Zielonyi, I.I.; Brezhnyeva, Yu.V.; Komarevtsev, V.N.; Shipilova, I.V. (World of Medicine and Biology, 2023)
Spontaneous preterm birth is the leading cause of perinatal morbidity and mortality worldwide. This problem has become especially relevant in the COVID-19 era. The purpose of the study was to investigate the association between serum alpha-1-antitrypsin levels and premature birth in COVID-19 and healthy pregnant women. Our study showed that serum alpha- 1-antitrypsin levels increase during normal pregnancy. We found that changes in alpha-1-antitrypsin concentrations are an important factor in preterm birth. Namely, there is an inverse relationship between alpha-1 antitrypsin levels and preterm birth: the lower the serum alpha-1 antitrypsin level, the higher the risk of preterm birth. In this study, we found that non-pregnant women with COVID-19 had a lower of alpha-1-antitrypsin levels then healthy non-pregnant women. In group pregnant women with COVID-19 with preterm birth level of α1-AT was approximately 1.5-fold lower in pregnant women with COVID-19 with timely delivery.